2019
DOI: 10.32098/mltj.04.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Double layer repair of tibialis anterior muscle hernia in a soccer player: a case report and review of the literature

Abstract: Background: muscle herniations usually present in athletes especially in the lower legs; occurring through defects in the deep fascial layer of the muscles and typically seen following local blunt trauma or muscle hypertrophy after strenuous exercise. Management of muscle hernias varies from conservative therapy to surgical repair and usually needs multidisciplinary collaboration for differential diagnosis. Methods: herein tibialis anterior muscle hernia in 17-year-old male soccer player was presented. The dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The relief of pain during the sixth postoperative week and the resumption of complete activity after the second month demonstrate that stability has been achieved and is coherent with the literature. The lack of recurrence in the long term and the disappearance of the pain alongside the regained functionality have been consistent with similar studies [20].…”
Section: Discussionsupporting
confidence: 91%
“…The relief of pain during the sixth postoperative week and the resumption of complete activity after the second month demonstrate that stability has been achieved and is coherent with the literature. The lack of recurrence in the long term and the disappearance of the pain alongside the regained functionality have been consistent with similar studies [20].…”
Section: Discussionsupporting
confidence: 91%
“…First, we presented a case of bilateral multiple TAMHs with traumatic neuromas of the SPN following fasciotomy. Several surgical procedures have been reported for the treatment of TAMH [ 2 , 4 , 5 , 6 , 7 , 8 , 15 ]. However, these previous studies were case series without high-level evidence, indicating no established surgical treatment for TAMHs.…”
Section: Discussionmentioning
confidence: 99%
“…When conservative treatments do not resolve the symptoms, surgical intervention is generally required. Available surgical options previously reported in academic papers include direct repair [ 4 ], repair using periosteum [ 5 ] or mesh [ 6 , 7 ] and fasciotomy [ 2 , 8 ]. These previous studies reported favorable clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal fasciotomy has been recommended 7. Repair with synthetic patches has been implemented 8. Despite various techniques, no recurrence rate for the condition after surgical treatment has been reported in the literature.…”
mentioning
confidence: 99%